Gender devlopment in Myanmar: an exploration of womens leadership trajectory - Dayaram, Kandy; Rola-Rubzen, Maria Fay; Burgess, John (2016)
Historically, in developing economies, the status and role of women were limited to and defined as that of ‘farmer’s wife’, positioning women’s work as unimportant and rendering women with very little decision-making powers. Over the last two decades, the status of women has changed in many ways; for instance women are now recognised as farmers in their own right. Women have also increasingly participated in paid labour. This shift in economic status has facilitated women’s empowerment and encouraged labour mobility allowing women to move from the agricultural sector to the manufacturing and services sector. Women are moving out of unpaid and informal employment into paid and formal employment. Myanmar as one of these developing economies is unique in its history and policy development, as noted in the report of Chhor et al. (2013: 4): “Myanmar is a very unusual case: a large country with a rich history that remains an underdeveloped agrarian economy in the heart of the world’s fastest-growing regional economy—perhaps one of the few remaining, largely untapped markets in the world.” The Organisation for Economic Co-operation and Development (Organisation for Economic Co-operation and Development [OECD] 2013) report states that whilst the overall labour participation in Myanmar is high at 78 per cent, approximately 70 per cent of the population are considered under-employed in the agricultural sector. Within this sector, whilst women’s labour participation in the workforce is high, they still face disadvantages compared to males. Despite its military rule and economic sanctions, women in Myanmar have endeavoured to forge career pathways into sectors outside of agriculture. In this chapter, we examine the strategies and practices that women deliberately seek to develop and empower themselves to assume leadership roles in the formal sector. Employing a qualitative analysis of interviews undertaken with women in leadership roles, the study explores the factors that contribute and influence gender development in Myanmar. It examines the challenges, perceived barriers and how these were overcome and the current practices that support women in leadership roles. These findings will be useful for government policymakers, planners and organisations that support the development of women.